Clinical Application of a Safe Blood Sampling Device with an Indwelling Needle. (1st September 2022) - Deng, Yeqin; Lv, Zhengbing; Cheng, Yue; Liu, Annuo; Huang, Zhengling
Abstract : Background . The traditional indwelling needle catheter is hard and can only complete one puncture at a time. The safety and indwelling needle catheter is soft, with a large lumen, with high success rate of blood collection, and one puncture completes two operations, so it is of important value and significance to study the new safety and indwelling needle. To explore the clinical utility of a novel blood collection device with indwelling needle for blood collection among pediatric patients. Methods . A total of 300 children who were admitted to the children's hospital from March to June 2020 were selected and randomly divided into the control group (148) and the observation group (152). The control group received venipuncture using regular needles for infusion and blood collection. For the observation group, a modified indwelling needle device was used for the procedures. Comparisons were made between the two devices in five aspects: blood sample quality, operation time, needlestick incidence, related complications, and patient satisfaction. Results . There was no significant difference in coagulation rate between the two groups, but slightly lower overall hemolysis incidence in the observation group. The unqualified rate of blood specimens collected in the observation group was 10.0% lower than that in the control group (P < 0.05 ). Shorter operation time, lower incidence of needlestick injuries, and improved satisfaction were observed in the group using the novel blood collection device. Conclusions . This modified blood collection device is superior to the regular venipuncture needle, in terms of safety, efficiency, and patient satisfaction; thus, it has potential for broad clinical applications for infusion and blood collection.